Prevalence of impaired renal function among rural and urban populations: findings of a cross-sectional study in Malawi [version 1; peer review: 1 approved, 2 approved with reservations] - Wisdom P Nakanga; Josephine E Prynn; Louis Banda; Robert Kalyesubula; Laurie A Tomlinson; Moffat Nyirenda; Amelia C Crampin (Wellcome Open Research, 2019)
Background: Sub-Saharan Africa faces region-specific risk factors for chronic kidney disease (CKD), such as nephrotoxic herbal medicines, antiretroviral therapy and infections, in addition to hypertension and diabetes. However, large epidemiological studies from this area are scarce. Methods: In a cross-sectional survey of non-communicable diseases, we conducted a prevalence sub-study of CKD in two Malawian populations. Study participants (N=5264) of 18 years of age and above were recruited and data on demographics and CKD risk factors were collected. Glomerular filtration rate was estimated (eGFR) using the CKD-EPI equation. Results: The prevalence of eGFR<60ml/min/1.73m2 was 1.4% (95% CI 1.1 – 1.7%) and eGFR<90ml/min/1.73m2 was 20.6% (95% CI 19.5 – 21.7%). The rural area had higher age-standardized prevalence of both eGFR<60ml/min/1.73m2, at 1.8% (95% CI 1.4 – 2.3) and eGFR <90 ml/min/1.73m², at 21.1% (95% CI 19.9 – 22.3), than urban location, which had a prevalence of 1.5%, (95% CI 1.0 – 2.2) and 19.4% (95% CI 18.0 – 20.8), respectively, with overlapping confidence intervals. The prevalence of CKD was lower in females than in males in both rural and urban areas. Older age (p < 0.001), a higher level of education (p = 0.03) and hypertension (p < 0.001) were associated with a higher adjusted odds ratio (aOR) of low eGFR. Diabetes was associated with a reduced aOR of eGFR<90ml/min/1.73m2 of 0.69 (95% CI 0.49–0.96; p=0.03). Of participants with eGFR<60ml/min/1.73m2, 14 (19.4%) had no history of hypertension, diabetes or HIV, while 36 (50%) had a single risk factor of being hypertensive. Conclusions: Impaired renal function is prevalent, but lower than expected, in rural and urban Malawi. Further research is needed to increase understanding of CKD incidence, survival and validation of eGFR calculations in this population.